Collaborative Care for Children: A Grand Rounds Presentation. (August 2014) - Foley, Michele; Dunbar, Nancy; Clancy, Jeanne
At the end of the 2011–2012 school year, two collaborative initiatives took place in Springfield, MA, between the public school system and Baystate Medical Center, an affiliate of Tufts University. The success of these initiatives was highlighted during grand rounds that featured academic medical center physicians and nurses as well as public school nurses. The program highlighted care of urban children with one of two chronic diseases, type 1 diabetes or asthma. Although the treatment and care of both these chronic childhood illnesses vary greatly, it is evident that primary care providers, school nurses, and students can benefit from increased collaboration, communication, and understanding of each other's roles. The partnerships were developed in an effort to overcome health care disparities that can and do exist in urban school districts such as Springfield, MA. In this commentary, we discuss important outcomes that resulted from the joint presentation at grand rounds.